Pengaruh Jenis Pupuk Organik Terhadap Pertumbuhan dan Hasil Serai Wangi (Cymbopogon nardus L.) Serta Beberapa Sifat Kimia dan Biologi pada Tanah Inceptisol - Ni Komang Rahayu Safitri; Ni Luh Kartini; Ni Nengah Soniari (Nandur, 2020)
This research aims at examining the effect of organic fertilizers towards the growth andyield of Citronella Grass on Inceptisol. The research was conducted for 8 months;January until September 2020 in Megati Village and at the Soil Science andEnvironment Laboratory Faculty of Agriculture, Udayana University. RandomizedBlock Design was applied in this research with eight treatments and four replicationsconsisting of PO0 = no fertilizer, PO1 = 2 kg for each clump of Vermicompost, PO2 = 2kg for each clump of Temesi Landfill compost, PO3 = 2 kg for each clump of WaterHyacinth compost, PO4 = 1 kg for each clump of Vermicompost + 1 kg for each clumpof Temesi Landfill Compost, PO5 = 1 kg for each clump of Vermicompost + WaterHyacinth Compost, PO6 = 1 kg for each clump of Temesi Landfill Compost + 1 kg foreach clump of Water Hyacinth Compost, PO7 = 0,65 kg for each clump ofVermicompost + 0,65 kg for each clumpof Temesi Landfill Compost + 0,65 kg for eachclump of Water Hyacinth Compost. The results of statistical analysis showed that theapplication of organic compost had a real impact on the number of Citronella Grasssaplings, its fresh weight, yield/hectare of Citronella Grass, N-total and disputablyaffected PH, C-organic, P-available, K-available, and the total population of soilmicroorganisme. The treatment of PO4 (1 kg for each clump of Vermicompostcombined with 1 kg for each clump of Temesi Landfill compost) showed that the freshweight of Citronella Grass is 1,4 kg which increased 55,5% compared to the controlwhich merely weights 0,9 kg.